QTLs for seedling traits under salinity stress in hexaploid wheat - Ren,Yongzhe (2018)
ABSTRACT: Soil salinity limits agricultural production and is a major obstacle for increasing crop yield. Common wheat is one of the most important crops with allohexaploid characteristic and a highly complex genome. QTL mapping is a useful way to identify genes for quantitative traits such as salinity tolerance in hexaploid wheat. In the present study, a hydroponic trial was carried out to identify quantitative trait loci (QTLs) associated with salinity tolerance of wheat under 150mM NaCl concentration using a recombinant inbred line population (Xiaoyan 54×Jing 411). Values of wheat seedling traits including maximum root length (MRL), root dry weight (RDW), shoot dry weight (SDW), total dry weight (TDW) and the ratio of TDW of wheat plants between salt stress and control (TDWR) were evaluated or calculated. A total of 19QTLs for five traits were detected through composite interval mapping method by using QTL Cartographer version 2.5 under normal and salt stress conditions. These QTLs distributed on 12 chromosomes explained the percentage of phenotypic variation by individual QTL varying from 7.9% to 19.0%. Among them, 11 and six QTLs were detected under normal and salt stress conditions, respectively and two QTLs were detected for TDWR. Some salt tolerance related loci may be pleiotropic. Chromosome 1A, 3A and 7A may harbor crucial candidate genes associated with wheat salt tolerance. Our results would be helpful for the marker assisted selection to breed wheat varieties with improved salt tolerance.